A practitioner's guide to data governance : a case-based approach - Gupta, Uma; Cannon, San (Emerald Publishing Limited, 2020)
Data governance looks deceptively simple on paper. In reality, it is complex. And it is increasingly recognized as a key foundational element necessary to advance analytics and improve operations for organizations of all types across industry. In this practical guide, data experts Uma Gupta and San Cannon look to demystify data governance through pragmatic advice based on real-world experience and cutting-edge academic research. Using case studies, the authors provide insight into how to address the myriad of data governance challenges facing organizations today, with useful and sensible actions and practices. The chapters focus on filling in the blanks of other data governance information, as well as providing both basic and forward-thinking suggestions for some of today's greatest challenges. It is peppered throughout with practical tips for data strategy, data literacy, and data quality. If you are new to data governance, or a seasoned practitioner looking to understand how to better address new issues, this book can help guide you through core elements such as communication, culture, and change management.
Includes index.
Keywords: Data protection.; Computers, Security -- General.; Privacy & data protection.; elektronické knihy; electronic books